2021
DOI: 10.1109/access.2021.3103512
|View full text |Cite
|
Sign up to set email alerts
|

A Template Approach for Summarizing Restaurant Reviews

Abstract: In the era of rapid development of social networks, user reviews of restaurant review websites have grown rapidly. In order to allow users to quickly grasp the key points of review information on review sites, this paper provides an abstractive multi-text summary method that can automatically generate template-based review summaries based on predefined topics and sentiments. In particular, for each predefined topic and each type of sentiment (positive or negative), this study uses the TextRank algorithm to fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…To evaluate the summaries, we adopted the BLEU and ROUGE metrics. Although these metrics are widely used for summarization tasks, evaluating summaries needs some kind of human judgment, as done in [3,34]. Moreover, when we analyzed how these algorithms work, we found that they have some limitations, as discussed in Section 4.5.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…To evaluate the summaries, we adopted the BLEU and ROUGE metrics. Although these metrics are widely used for summarization tasks, evaluating summaries needs some kind of human judgment, as done in [3,34]. Moreover, when we analyzed how these algorithms work, we found that they have some limitations, as discussed in Section 4.5.…”
Section: Discussionmentioning
confidence: 98%
“…Review datasets should also include human summaries, preferably by more than one native Arabic speaker. Nevertheless, other qualitative methods should be considered for evaluating summaries, such as those suggested in [3,35]. Different approaches, including deep learning, could be investigated and compared with graph-based methods.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations